Perkawinan Di Bawah Umur Dalam Perspektif Undang-Undang Perkawinan Dan Undang-Undang Perlindungan Anak - Virna Atikasari; Eti Mul Erowati; Elisabeth Pudyastiwi (Faculty of Law, Universitas Wijayakusuma, 2020)
ABSTRACT The objectives of this thesis are: to determine the arrangement of underage marriages with Law no. 1 of 1974 concerning Marriage and to determine the legal protection of children who are married under age in accordance with Law no. 23 of 2002 concerning child protection. The research method uses qualitative methods, normative juridical approach, descriptive analytical research specifications, secondary data collection with materials through literature review, analysis using normative qualitative methods, data presentation is presented in systematic descriptions. The practice of underage marriage needs to be considered and clearly defined, because there are more and more people in Indonesia who are married underage. The conclusions are: there is no legal synchronization, especially related to underage marriage according to Law Number 16 of 2019 concerning amendments to Law Number 1 of 1974 concerning Marriage with the Child Protection Law as statutory regulation in set a minimum age limit for the parties to marry. The Marriage Law has not yet been sanctioned for violators because there are regulations on marriage dispensation listed in article 7 paragraph 2 of Law Number 16 of 2019 concerning amendments to Law Number 1 of 1974 concerning Marriage, but in Law The Child Protection Law already has sanctions for violators. Second, the Child Protection Law has provided legal protection for children who are married under age, which is regulated in Article 78, Article 82 and Article 88 of the Child Protection Law. Keywords: Underage Marriage, Child Protection, Law no. 1 of 1974 concerning marriage, Law no. 23 of 2002 concerning child protection. Abstrak. Tujuan dari skripsi ini, yaitu untuk menentukan pengaturan perkawinan di bawah umur dengan UU No. 1 tahun 1974 tentang perkawinan dan untuk menentukan perlindungan hukum terhadap anak-anak yang melakukan perkawinan di bawah umur sesuai dengan UU No. 23 tahun 2002 tentang perlindungan anak. Metode penelitian menggunakan metode kualitatif, pendekatan yuridis normatif, spesifikasi penelitian deskriptif analitis, pengambilan data sekunder dengan bahan melalui kajian kepustakaan, analisis dengan metode kualitatif normatif, penyajian data disajikan dalam uraian-uraian yang tersusun secara sistematis. Praktik perkawinan di bawah umur perlu diperhatikan dan ditetapkan dengan jelas, karena ada lebih banyak lagi orang di Indonesia yang menikah di bawah umur. Kesimpulan yaitu : belum adanya sinkronisasi hukum terutama terkait dengan perkawinan di bawah umur menurut Undang-undang Nomor 16 Tahun 2019 tentang perubahan atas Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan dengan Undang-Undang Perlindungan Anak sebagai peraturan perundang-undangan dalam menetapkan batas minimum umur bagi pihak-pihak untuk melakukan perkawinan. Undang-Undang Perkawinan belum ada sanksi bagi yang melanggar karena ada peraturan tentang dispensasi perkawinan yang tercantum dalam pasal 7 ayat 2 Undang-undang Nomor 16 Tahun 2019 tentang perubahan atas Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan, tetapi pada Undang-Undang Perlindungan Anak sudah ada sanksi bagi pelanggarnya. Kedua, Undang-Undang Perlindungan Anak sudah memberikan perlindungan hukum terhadap anak yang melakukan perkawinan di bawah umur, yang diatur dalam Pasal 78, Pasal 82 dan Pasal 88 Undang-Undang Perlindungan Anak.Kata Kunci : Perkawinan Di Bawah Umur, Perlindungan Anak, UU No. 1 tahun 1974 tentang perkawinan, UU No. 23 tahun 2002 tentang perlindungan anak.